Estrategias de evaluación de los Aprendizajes para promover la inclusión Educativa en estudiantes de la Carrera de Ingeniería Informática (Repertorio Científico, 2025)
For UNED, the purpose of higher education means academic inclusion as part of the recognition of diversity, creation of accessible environments and equal opportunities, to all sectors of the population. In this sense, for the Systems Development and Systems Technology Chairs, is important to apply inclusion in the evaluation of learning for the 44 students who are enrolled in the Program for Special Educational Needs of the Universidad Estatal a Distancia. The above leads to a planning of the learning evaluation process by the chairs to offer accessibility to this population, with the different evaluation instruments, as well as the virtual campus or LMS, and the programming languages that must be used in the subjects. As a learning strategy, the departments use NVDA software, which is a free and open source screen reader for the Microsoft Windows® Operating System, is used by some students with special needs, for electronic reading of documents, screens and the LMS platform, in addition to applying Universal Learning Design (UDL). This has contributed to the provision of strategies and the promotion of new experiences, as a reference for the different areas that make up the computer engineering degree, promoting the active participation of students, teachers and department managers with the purpose of facilitating quality access in an inclusive and equitable environment
Keywords: accessibility, inclusion, distance education, disability, computer programming, learning context.